Curcuma Longa: Nutraceutical Use and Association With Nanotechnology - Corrêa Carvalho, Gabriela [UNESP]; Marena, Gabriel Davi [UNESP]; Gaspar Gonçalves Fernandes, Micaela; Ricci Leonardi, Gabriela [UNESP]; Santos, Hélder A.; Chorilli, Marlus [UNESP] (Wiley, 2024)
Curcumin is a natural product found in the rhizome of Curcuma longa (L.) and other Curcuma spp. As a lipophilic molecule, it has greater affinity for polar, non-polar, alkaline, or extremely acidic organic solvents. Several studies indicate that curcumin has several benefits for human health, for example, against degenerative diseases, cancer, and infectious diseases. To obtain a quality product with nutraceutical properties, it is necessary to know its physicochemical characteristics and preserve it from cultivation until ingestion by the human. However, its low solubility leads to low absorption; in this context, nanotechnological systems can contribute to increase curcumin bioavailability. This review aims to highlight important issues in all stages that curcumin goes through: from aspects related to its extraction to its association with nanotechnology. Although curcumin extraction process is already well established, it is possible to observe more and more research focused on increasing yield and being more environmentally friendly. Further, curcumin's low absorption is notable due to its physicochemical characteristics, mainly due to its low aqueous solubility. However, its association with nanotechnology shows to be promising and an increasingly growing trend because the use of this “Indian solid gold” is the hope of many patients.
Keywords: analytical methods; biological activity; extraction processes; nanocarriers; natural product; polyphenol